2013
DOI: 10.1177/1457496913482234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Health-related Quality of Life in Patients with Narrow Gastric Tube and Whole Stomach Reconstruction after Oncologic Esophagectomy: A Prospective Randomized Study

Abstract: Background andResults: The perioperative complication rate was 26.9% in narrow gastric tube group and 48.1% in whole stomach group (P = 0.31). At the time of 3 weeks after surgery, the reflux and dyspnea scores were higher in whole stomach group than in narrow gastric tube group, which meant that the patients in whole stomach group suffered more severe problem. At the time of 6 months and 1 year after surgery, the reflux scores were lower in narrow gastric tube group than in whole stomach group, which revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…76 Out of the 58 studies, 42 studies have used the EORTC QLQ-C30 as measurement for QOL after surgery for esophageal cancer. Disease-specific modules can be added, the EORTC QLQ- 13 1 14 1 15 1 16 1 17 1 0 OESophagus (OES18) and the EORTC QLQ-OES24 are modules for esophageal cancer. The EORTC QLQ-OES24 was replaced by a refined shorter EORTC QLQ-OES18, which depicted good clinical and psychometric validity.…”
Section: The Quality Of Life Instrumentsmentioning
confidence: 99%
“…76 Out of the 58 studies, 42 studies have used the EORTC QLQ-C30 as measurement for QOL after surgery for esophageal cancer. Disease-specific modules can be added, the EORTC QLQ- 13 1 14 1 15 1 16 1 17 1 0 OESophagus (OES18) and the EORTC QLQ-OES24 are modules for esophageal cancer. The EORTC QLQ-OES24 was replaced by a refined shorter EORTC QLQ-OES18, which depicted good clinical and psychometric validity.…”
Section: The Quality Of Life Instrumentsmentioning
confidence: 99%
“…180 A recent trial reported that patients given narrow gastric tube reconstruction experienced less trouble with reflux at one year after the operation than patients given whole stomach reconstruction. 181 Fatigue is a common problem for cancer survivors. Physiological and psychological mechanisms, e.g.…”
Section: Study I -Hrqol Recovery At Long-termmentioning
confidence: 99%
“…After total thoracic esophagectomy for esophageal cancer, reconstruction typically involves the stomach and the placement of a narrow gastric tube. 6 However, pulling up this narrow gastric tube is difficult. If graft necrosis develops, anastomotic leakage or mediastinitis is nearly inevitable.…”
Section: Discussionmentioning
confidence: 99%